KOMPLIKASI EMBOLI PARU PADA CORONA VIRUS DISEASE 2019 (COVID – 19) : Sebuah Tinjauan Literatur - Nurdianto, Arif Rahman (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2021)
Background: The respiratory disease that attacks respiratory system makes a high mortality rate which one of the complications of its manifestation is thrombotic in the amount of 31% , where from all these complications, 87% of which are pulmonal embolic. It is an emergency state that can cause death and as it needs fast, accurate diagnostic and handling for better outcome for the patients.MethodThis Study compares many sources form research articles, case reports, and international journal reviews.Result: Scoring, D dimer, and the other imaging examination that available at health center can be used together for Covid 19 screening to find out pulmonal embolism as a Covid 19 complication.Conclusion: the accurate dan precise pulmonal embolism in Covid 19 used scoring and imaging that available in the health center makes the prompt treatment dan makes a better outcome.